Business Ethics from the Qur'an Perspective - Muhammad Irza Irsyadillah (Penerbit Hellow Pustaka, 2025)
There are still many Muslim communities who consider business ethics to be of little importance in business activities, because business is nothing but to seek profit. Through this research will be discussed how business ethics in the perspective of the Koran. This research includes library research (library research), namely research that examines data sourced from library materials, using the thematic interpretation method. This research is based on the interpretation of verses of the Koran that directly discuss business ethics and verses that do not directly discuss business ethics. Business in the Qur'an is both material and immaterial. Where business in the Qur'an does not only prioritize material profits but also spiritual benefits. The existence of business ethics cannot be separated from the business itself. The Qur'an's business ethics contain basic business values such as the values of unity, balance, free will, accountability, and ihsan. Then it gives birth to business ethics which are free from evil, corruption and tyranny such as usury practices, fraud, reducing doses or fraud, corruption, bribery, gambling, gharar and hoarding and so on. Then business in the Koran emphasizes hasanah values such as honesty, trustworthiness, fairness, social responsibility, istiqomah, tolerance and friendliness in business life. Thus business ethics in the Koran are not only oriented towards meeting the needs and welfare of life in the world, but also business as a warehousing for good for safety in the hereafte.